Global Liquidity : Issues for Surveillance. (Policy Papers; Policy Paper ;, 2014)
The paper starts by presenting evidence of commonality in global financial conditions. This commonality is then related to specific drivers of global financial conditions through a range of transmission channels, including cross-border banking and portfolio flows. Empirical analysis shows a range of price and quantity factors, including measures of risk, bank leverage, and interest rates in financial centers, to drive in part these flows. Country specific policies, including exchange rate and prudential frameworks, are shown to affect the transmission of global conditions. Much remains unknown though, including how evolving structures of global funding, changing institutions, and ongoing financial innovations affect the mechanics of liquidity creation, the channels of liquidity transmission, and potential risks going forward.